2023
DOI: 10.2196/49220
|View full text |Cite
|
Sign up to set email alerts
|

Appraising Unmet Needs and Misinformation Spread About Polycystic Ovary Syndrome in 85,872 YouTube Comments Over 12 Years: Big Data Infodemiology Study

Kashish Malhotra,
Punith Kempegowda

Abstract: Background Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women, resulting in substantial burden related to metabolic, reproductive, and psychological complications. While attempts have been made to understand the themes and sentiments of the public regarding PCOS at the local and regional levels, no study has explored worldwide views, mainly due to financial and logistical limitations. YouTube is one of the largest sources of health-related information, where many visitors s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Though the challenge was debunked as a hoax, concerned parents still viewed videos about this topic on YouTube as reported in prior works in this field [61,62]. In an analysis of YouTube videos about polycystic ovarian syndrome (PCOS), Malhotra et al [63] analyzed comments using the Benjamini-Hochberg Procedure and sentiments with SentiStrength. The analysis revealed that men and women had different feelings about PCOS with men being more heavily associated with misinformation about home remedies or a cure.…”
Section: Review Of Misinformation Analysis On Youtubementioning
confidence: 99%
“…Though the challenge was debunked as a hoax, concerned parents still viewed videos about this topic on YouTube as reported in prior works in this field [61,62]. In an analysis of YouTube videos about polycystic ovarian syndrome (PCOS), Malhotra et al [63] analyzed comments using the Benjamini-Hochberg Procedure and sentiments with SentiStrength. The analysis revealed that men and women had different feelings about PCOS with men being more heavily associated with misinformation about home remedies or a cure.…”
Section: Review Of Misinformation Analysis On Youtubementioning
confidence: 99%
“…Common misconceptions, such as PCOS being solely a reproductive issue or a consequence of lifestyle choices, need to be debunked through accurate and accessible information. Empowering individuals with knowledge is crucial to dispelling myths and instrumental in fostering a sense of agency and control over their health [10].…”
Section: The Need To Dispel Myths and Misinformationmentioning
confidence: 99%
“…Increased use of social media correlates with a higher probability of individuals interacting with different forms of content, including deceptive or inaccurate information [ 32 ]. Exposure to this digital information environment can modify a person’s beliefs and decision-making processes surrounding health care, potentially resulting in unmet need for medical care [ 33 34 ].…”
Section: Introductionmentioning
confidence: 99%